Risk Factors for Unplanned Readmissions Following Excisional Breast Surgery. Issue 3 (2nd April 2014) - Khavanin, Nima; Bethke, Kevin P; Lovecchio, Francis C; Jeruss, Jacqueline S; Hansen, Nora M; Kim, John YS
Abstract Thirty‐day hospital readmission has emerged as an important variable in health care quality improvement. Our purpose was to investigate the unplanned readmission rate following excisional breast surgery and to identify risk factors associated with readmission. The 2011 National Surgical Quality Improvement Program registry was retrospectively reviewed for patients undergoing excisional breast surgery. Logistic regression was used to investigate the relationship between pre‐ and perioperative variables and 30‐day readmission. Of 13, 610 women identified, 292 (2.15%) were readmitted within the 30‐day tracking period. The readmitted cohort demonstrated significantly more comorbidities and postoperative complications, as well as longer operative times and hospital stays. Postoperative complications were the best predictors for readmission; however, age, a history of bleeding disorders, immunosuppression, cardiovascular disease, and inpatient hospitalization were also significant independent predictors for readmission. Risk factors for readmission include both pre‐ and perioperative variables. Perioperative complications, most often infectious in nature, are the strongest predictors; however, comorbidities including immunosuppression, bleeding disorders, and cardiovascular disease also significantly increase the risk for readmission. Although readmission is relatively rare, identifying and managing high‐risk patients in addition to more effective methods to prevent and manage postoperative complications will be critical to reducing readmissions and improving patient care.